Pengaruh Profitabilitas dan Leverage Terhadap Nilai Perusahaan Pada PT Bank Central Asia Tbk Yang Terdaftar Di Bursa Efek Indonesia Tahun 2015 – 2024 - Gulo, Yanto Nius; Setiawan, Arip Budi (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
This This study aims to analyze the effect of Profitability and Leverage on Firm Value at PT Bank Central Asia Tbk, which is listed on the Bursa Efek Indonesia, during the 2014–2024 period. This research employs a quantitative approach with an associative research design. The data used are secondary data in the form of the company’s annual financial statements over the eleven-year research period. All financial data during this period were used as both the population and the sample of the study. The data analysis technique applied was multiple linear regression using SPSS version 27 software. The results show that simultaneously, Profitability and Leverage do not have a significant effect on Firm Value. This is evidenced by the F-test significance value of 0.189, which is greater than 0.05. Thus, it can be concluded that the two independent variables, when considered together, are not able to significantly explain variations in Firm Value. Partially, Profitability does not have a significant effect on Firm Value, with a t-test significance value of 0.086, which is greater than 0.05. However, the positive regression coefficient indicates that Profitability has a positive direction of relationship with Firm Value. Meanwhile, Leverage also does not have a significant effect on Firm Value, with a t-test significance value of 0.256, which is greater than 0.05. The negative regression coefficient indicates that Leverage has a negative direction of relationship with Firm Value. These findings indicate that during the research period, Profitability and Leverage were not the main determinants influencing Firm Value.